Platelet Aggregation Induced in Vitro by Therapeutic Ultrasound - Chater, B. V; Williams, A. R (Thrombosis and Haemostasis, 1977)
Platelets were found to aggregate spontaneously when exposed to ultrasound generated by a commercial therapeutic device. At a given frequency, aggregation was found to be a dose-related phenomenon, increasing intensities of ultrasound inducing more extensive and more rapid aggregation. At any single intensity, the extent aggregation was increased as the frequency of the applied ultrasound was decreased (from 3.0 to 0.75 MHz).Ultrasound-induced platelet aggregation was found to be related to overall platelet sensitivity to adenosine diphosphate. More sensitive platelets were found to aggregate spontaneously at lower intensities of sound, and also the maximum extent of aggregation was found to be greater. Examination of ultrasound-induced platelet aggregates by electron microscopy demonstrated that the platelets had undergone the release reaction.The observation that haemoglobin was released from erythrocytes in whole blood irradiated under identical physical conditions suggests that the platelets are being distrupted by ultrasonic cavitation (violent gas/bubble oscillation).It is postulated that overall platelet aggregation is the result of two distinct effects. Firstly, the direct action of ultrasonic cavitation disrupts a small proportion of the platelet population, resulting in the liberation of active substances. These substances produce aggregation, both directly and indirectly by inducing the physiological release reaction in adjacent undamaged platelets.